Effect of core training on athletic and skill performance of basketball players: A systematic review. - Shengyao Luo; Kim Geok Soh; Yanmei Zhao; Kim Lam Soh; He Sun; Nasnoor Juzaily Mohd Nasiruddin; Xiuwen Zhai; Luhong Ma (PLoS ONE)
A limited number of studies focus on the effect of core training on basketball players' athletic performance and skills. This systematic reviewaimed to comprehensively and critically review the available studies in the literature that investigate the impact of core training on basketball players' physical and skill performance, and then offer valuable recommendations for both coaches and researchers. Thedata collection, selection, and analysis adhered to the PRISMA protocol. English databases, including Ebscohost, Scopus, PubMed, Web of Science, and Google Scholar,were searched until September 2022. A total of eight articles were included, with four studies comparing the effects of core training versus traditional strength training or usual basketball training. All studies investigated the impact of core training on athletic performance. The findings revealed that core training can help players improve their overall athletic and skill performance, particularly in the areas of strength, sprinting,jumping, balance, agility, shooting, dribbling, passing, rebounding, and stepping. In addition, core training, particularly on unstable surfaces,as well as combining static and dynamic core training,improvebasketball players' athletic and skill performance. Despite the relativelylittle evidence demonstrating the effect of core training on endurance, flexibility, and defensive skills, this review demonstrates that it should be incorporated into basketball training sessions.